Increased subsequent risk of erectile dysfunction in patients with irritable bowel syndrome: a nationwide population‐based cohort study. (22nd August 2013) - Chao, C.‐H.; Lin, C.‐L.; Wang, H.‐Y.; Sung, F.‐C.; Chang, Y.‐J.; Kao, C.‐H.
Summary: This retrospective population‐based study aimed to investigate associations between erectile dysfunction (ED) and the irritable bowel syndrome (IBS) using a Taiwanese cohort. We identified 17 608 male patients who were newly diagnosed with IBS from 1997 to 2010. The date that the diagnosis of IBS had been made was the index date. IBS patients with a history of ED before the index date or with incomplete demographic information were excluded. 70 432 age‐matched subjects without IBS were selected as comparison cohort. Both cohorts were followed until the end of 2010 or censored. Cox proportional hazard regression model was used to estimate the effects of IBS on ED risks. The incidence rate ratio of ED in the IBS cohort was 2.92 times higher than that in the non‐IBS cohort (29.5 vs. 10.1 per 10 000 person‐years), with an adjusted hazard ratio (aHR) of 2.58 (95% confidence interval [CI]: 2.24–2.98). The risk of ED increased with increasing age and number of comorbidities. Patients with depression were at a higher risk of ED (aHR: 1.97; 95% CI: 1.49–2.63) compared with the subjects without depression. IBS patients had a higher risk of developing ED compared with non‐IBS subjects. Ageing and comorbidities including diabetes, cardiovascular disease, chronic kidney disease and depression were associated with the risk of ED.